The cell as secret agent—autonomy and intelligence of the living cell: driving force of development - Brian J. Ford (Academia Biology)
The related disciplines of ecology and evolution pay little heed to the essential driver of development, the single living cell. We cannot comprehend the realities of population dynamics and evolutionary impetus without the cell being at the heart of our considerations. Biologists emphasize the importance of the organism, and imperatives derived from Cartesian reductionism underpin contemporary interpretations of multicellular organisms and the manifestation of life in protists. We search for increased resolution and greater magnification; however, the crucial contribution of the entire single living cell is conventionally overlooked. Our failure to elucidate the mechanisms underpinning the phenomenology of response in the living cell is seen as a failure to interpret the physics of metabolic and sensory processes, but life transcends physics. The responsive behavior of living cells and their ability to solve novel problems have not been resolved, and our standard model physics is itself not up to the task. It is here posited that living organisms survive and proliferate through complex mechanisms inimical to conventional scientific analysis. To watch life at work it is the lower-power lens we need, not the high-resolution microscope.